The development of random thinking using a playful strategy as a pre-exercise in fourth and fifth grade students. (2022)
This document addresses the subject of Random Thinking using a playful strategy as a pre-exercise, this study is developed with students in the fourth and fifth grades of the Loma de Tigre campus in San Isidro de Chichimene, where the objective is to “Develop random thinking and data system in fourth and fifth year students using play as a pre-exercise to improve the performance of mathematical thinking in elementary school at the Loma de Tigre campus ”study that was carried out according to the precepts of the research Mixed with a descriptive approach, it was taken as theoretical references to Polya, Batanejo, Piaget, among others, who contemplate aspects inherent to the learning of mathematics and the development of the person, which allowed to combine these two aspects and from there to design the proposal of intervention, from where it was possible to obtain results on the initial level of the students in the management of random thinking, or Once they were intervened with the proposed activity, the exit test was applied again and the comparison was made, achieving as results that the project left a positive impact on the students and they significantly improved in the mastery and management of random thinking. It is concluded that it is important and timely to work on mathematics from research and exploration that allows students to achieve concepts and procedures that are to be used for their academic and work life.